Effect of Mixed Corrosion Inhibitors in Cooling Water System - Raheem, Dina (Al-Khwarizmi Engineering Journal, 2011)
The effect of mixed corrosion inhibitors in cooling system was evaluated by using carbon steel specimens and weight loss analysis. The carbon steel specimens immersed in mixture of sodium phosphate (Na2 HPO4) used as corrosion inhibitor and sodium glocunate (C6 H11 NaO7) as a scale dispersant at different concentrations (20,40, 60, 80 ppm) and at different temperature (25,50,75 and 100)ºC for (1-5) days. The corrosion inhibitors efficiency was calculated by using uninhibited and inhibited water to give 98.1%. The result of these investigations indicate that the corrosion rate decreases with the increase the corrosion inhibitors concentration at 80 ppm and at 100ºC for 5 days, (i.e, corrosion rate= 0.014gmd).